O controle de autoridade no domínio bibliográfico: os catálogos em livros e em fichas - Assumpção, Fabrício Silva [UNESP]; Da Costa Santos, Plácida Leopoldina Ventura Amorim [UNESP]; Zafalon, Zaira Regina (University Library System, University of Pittsburgh, 2017)
In this paper we use a literature review to analyze the authority control and the role of authority data in book and card catalogs. Considering the ambiguity in the relation among the entities used as access points in catalogs (persons, corporate bodies, concepts, etc.) and the names by which these entities are known, we discuss authority control and the concepts related to it. Then, we describe book catalogs and card catalogs focusing on their arrangement and access points, and we highlight the main contributions of Panizzi, Jewett, Cutter, and American Library Association related to authority control. As conclusions, we point out that current authority records had their functions and elements defined in analogic catalogs context, especially in card catalogs. The results presented in this paper contribute to understanding of the current authority records and files and of the authority control concept itself, as well as they support the discussion about new descriptive rules, data interchange standards, practices and technologies used in the publication of bibliographic and authority data.
Authority control in the bibliographic domain: Book and card catalogs
Keywords: Authority control; Bibliographic catalogs; Book catalogs; Card catalogs; Descriptive cataloging; History of cataloging